The Effect of Economic Growth, Investment and Unemployment on Poverty in Sulawesi Island from 2010 to 2024 - Desti Saputri; Asep Munir Hidayat; Billy Tejaarief; Kenedi Kenedi; Anti Wulan Agustini (Transpublika Publisher, 2025)
Poverty remains an obstacle that continues to disrupt social welfare among communities on the island of Sulawesi. The objectives of this study are to determine the long-term effects of economic growth, investment and unemployment on poverty in Sulawesi Island; to examine the short-term effects in each province in Sulawesi Island; to determine whether there is an error correction adjustment mechanism; and to determine whether there is a causal relationship between economic growth and poverty. This study uses the Secondary Data Analysis (SDA) method with a quantitative correlational approach and uses the ARDL Panel analysis model. The study's outcomes reveal that economic growth, investment, and unemployment significantly reduce poverty across Sulawesi Island when examined over extended periods. Short-term provincial variations emerge as follows: North Sulawesi and Central Sulawesi experience positive effects from all three factors. In South Sulawesi and Southeast Sulawesi, economic growth and investment demonstrate negative effects, whereas unemployment shows positive effects. Gorontalo exhibits positive effects from economic growth and unemployment, though investment produces negative effects. West Sulawesi presents a mixed pattern, with economic growth reducing poverty while investment and unemployment increase it. Although error correction adjustments function across all provinces, only West Sulawesi demonstrates statistically significant adjustment processes. There is a causal relationship between economic growth and poverty. Equitable economic growth and investment can certainly be felt by the poor, thus opening up opportunities to increase productivity, and vice versa. Meanwhile, unemployment certainly has a significant impact on poverty.